ANALISIS KUALITAS PELAYANAN DALAM MENINGKATKAN KEPUASAN PELANGGANJNT EXPRESS CABANG CILINCING DIMASA PANDEMI COVID-19 - Ledi Diana; Muhammad Asad (JAMBIS : Jurnal Administrasi Bisnis, 2022)
One of the service industries that is experiencing dynamics in its development is the Cilincing Outlet of PTJ&T Express, a freight and document delivery service that has been established since August 2015. This research was motivated by the Covid-19 pandemic which caused a decline in the number of J&T customers.The purpose of this study is to determine the quality of service to customers, the factors that hinder service, and the efforts made by the Cilincing Outlet of PT J&T Express in improving service quality during the Covid-19pandemic. This study used five independent variables, namely tangible, reliability, responsiveness, assurance and empathy, and one dependent variable, namely customersatisfaction. Informants in this study were employees and customers of the Cilincing Outlet of J&T Express. Key informants consisted of 8 respondents who were selected using non-statistical analysis, namely the analysis used for qualitative data. Based on interviews, observations and documentation studies, the results of research show that based on physical evidence (tangible), reliability, responsiveness, assurance and empathy, not all services at the Cilincing Outlet of J&T Express run well. The causes include, among others, employees with slow performance and inadequate facilities and infrastructure. As a result, the number of customers is decreasing.